1997
DOI: 10.1177/036354659702500416
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Anterior Cruciate Ligament Reconstruction in Middle-Aged Patients

Abstract: The purpose of this study was to evaluate the results and complications of anterior cruciate ligament surgery in middle-aged patients. Forty-five consecutive pa tients over 40 years old (average age, 44.6 years) who had arthroscopically assisted anterior cruciate liga ment reconstructions with midthird patellar tendon au tografts were evaluated. The patients returned for in terviews, physical examinations, radiographs, Biodex dynamometer strength testing, and KT-1000 arthrom eter testing at an average of 37 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 27 publications
6
37
0
Order By: Relevance
“…Recently several authors [1, 3,6,9,11] found similar results in motivated patients over 40 years old to those in younger patients. Barber et al [3] compared two groups of patients, under and over 40 years old, and concluded that the outcomes were the same.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Recently several authors [1, 3,6,9,11] found similar results in motivated patients over 40 years old to those in younger patients. Barber et al [3] compared two groups of patients, under and over 40 years old, and concluded that the outcomes were the same.…”
Section: Introductionsupporting
confidence: 61%
“…Older patients were treated by guided rehabilitation and were strongly urged to modify their physical activities [4,7]. Some extra-articular procedures were performed in selected cases [14], but the long-term results were poor.Recently several authors [1, 3,6,9,11] found similar results in motivated patients over 40 years old to those in younger patients. Barber et al [3] compared two groups of patients, under and over 40 years old, and concluded that the outcomes were the same.…”
supporting
confidence: 61%
“…2,5,13 However, many authors have demonstrated that the outcomes of ACL reconstruction in middle-aged or elderly patients were satisfactory, some of them comparable with those of younger patients. [1][2][3]5,8,11,13,17 Given the results, age does not appear to affect the outcome of ACL reconstruction. Rather, the status of articular cartilage might be a more important predictor of outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…19,25,40 The KT-1000 arthrometer and functional testing were performed by a certified athletic trainer/physical therapist who was not involved with surgical treatment, and 30 lb of force was selected to compare side-to-side measurements. 13 were allowed to warm up, and the hop was graded as a mean of 3 attempts. It has been shown that the singlelegged hop is associated not only with functional outcome in the ACL-reconstructed knee but also with isokinetic quadriceps peak torque at 180 and 300 deg/s.…”
Section: Discussionmentioning
confidence: 99%